2006
DOI: 10.1111/j.1399-0039.2006.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐C molecular characterization of a Lebanese population and genetic structure of 39 populations from Europe to India–Pakistan

Abstract: Lebanon is located at a continental crossroad between Europe, Africa, and Asia. This region has been the center of wide-scale movements of populations as well as the theater of genetic and cultural trade off among neighboring populations. In this study, HLA-C alleles were characterized by a PCR-SSOP (sequence-specific oligonucleotide probes) hybridization protocol in a sample of 97 Lebanese. A total of 23 alleles were identified with four predominant, Cw*0401, Cw*0602, Cw*0701/06, and Cw*1203, accounting for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
10
18
0
Order By: Relevance
“…While encompassing a restricted geographic area, Switzerland is a region of great interest in Europe from a genetic point of view, as it is centrally located and embraces two very distinct environments, north/north-western lowlands (the Central Plateau) and south/south-eastern highlands (the Alps), in addition to another softly mountainous region in the north (the Jura). Therefore, this country may lie at the boundary of an abrupt genetic variation of HLA frequencies previously observed between north-western and south-eastern Europe, and tentatively explained by the presence of the Alps as a geographic barrier to gene flow [26], [29]. Moreover, Switzerland is characterized by an important cultural diversity, with three main languages spoken, French, German and Italian, and a fourth minor national language, Romansh.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…While encompassing a restricted geographic area, Switzerland is a region of great interest in Europe from a genetic point of view, as it is centrally located and embraces two very distinct environments, north/north-western lowlands (the Central Plateau) and south/south-eastern highlands (the Alps), in addition to another softly mountainous region in the north (the Jura). Therefore, this country may lie at the boundary of an abrupt genetic variation of HLA frequencies previously observed between north-western and south-eastern Europe, and tentatively explained by the presence of the Alps as a geographic barrier to gene flow [26], [29]. Moreover, Switzerland is characterized by an important cultural diversity, with three main languages spoken, French, German and Italian, and a fourth minor national language, Romansh.…”
Section: Introductionmentioning
confidence: 83%
“…In this study, the Swiss Blood Stem Cells (SBSC) registry has been used to explore in detail the HLA genetic variation throughout Switzerland, for which few results have been published until now [26], [27], [28]. While encompassing a restricted geographic area, Switzerland is a region of great interest in Europe from a genetic point of view, as it is centrally located and embraces two very distinct environments, north/north-western lowlands (the Central Plateau) and south/south-eastern highlands (the Alps), in addition to another softly mountainous region in the north (the Jura).…”
Section: Introductionmentioning
confidence: 99%
“…transplantation) purposes, but it has seldom been used to study the genetic variation among populations. Many studies have shown that the HLA polymorphism is very informative to reconstruct past human migration events [19], [20], [21], [22], [23], [24], [25]. However, these works are based on the interpretation of allelic frequency distributions, with all alleles being considered as equidistant molecular units in each population; the main reason being that there is still a lot of uncertainty associated to HLA molecular typings due to the extreme level of polymorphism at these loci.…”
Section: Introductionmentioning
confidence: 99%
“…1 ), may have resulted from reduced gene flow across the Alps. Indeed, a significant genetic boundary has previously been detected in this region through HLA comparisons, both at the continental scale [36] and at the country level [i.e. Switzerland, 66 ].…”
Section: The Signatures Of Demographymentioning
confidence: 99%
“…The total number of individuals per locus varied between 1,582 and 125,889 (also depending on the resolution level considered). This database includes data from the 12th, 13th, 15th and 16th International Histocompatibility workshops [22][23][24][25]34] , the 'HLA-NET' project [35] and other published sources [36][37][38][39] (online suppl. table S1 and suppl.…”
Section: Population Datamentioning
confidence: 99%